International Reflections on the Netherlands Didactics of Mathematics Visions on and Experiences with Realistic Mathematics Education - van den Heuvel-Panhuizen, Marja (ICME-13 Monographs,, 2020)
This open access book, inspired by the ICME 13 Thematic Afternoon on "European Didactic Traditions", takes readers on a journey with mathematics education researchers, developers and educators in eighteen countries, who reflect on their experiences with Realistic Mathematics Education (RME), the domain-specific instruction theory for mathematics education developed in the Netherlands since the late 1960s. Authors from outside the Netherlands discuss what aspects of RME appeal to them, their criticisms of RME and their past and current RME-based projects. It is clear that a particular approach to mathematics education cannot simply be transplanted to another country. As such, in eighteen chapters the authors describe how they have adapted RME to their individual circumstances and view on mathematics education, and tell their personal stories about how RME has influenced their thinking on mathematics education.